An Analysis of Students' Ability in Writing Descriptive Composition in Vocational High School - Yuni Miratun Barokah; Eline Rozaliya Winarto; Ikariya Sugesti (National Conference on Language, Education, and Technology Proceeding, 2021)
In writing descriptive composition students still experience deficiencies, where some students still find it difficult to write. The purpose of study is to find out the students' abilities in writing descriptive composition and what that difficulties students face in writing descriptive composition in Vocational High School. This research was conducted by qualitative research using descriptive method. The subject of this research are students of class X OTKP in one of private school in Cirebon. There are 19 students in the class and researcher choses 14 students with a random technique. Furthermore, the researcher used student writing and interviews as instruments. The researcher analyzed the data, and the researcher found some finding in the field. First, it was found that the students' ability in writing descriptive compositions was at a low level. This is supported by the second finding, the results of interviews with students, namely that students' difficulties are the generic structure of descriptive composition which consists of describing objects in detail and grammar. In addition, most students have difficulty in arranging words into sentences and writing the correct spelling of words. In addition, the lack of vocabulary makes them write many repetitions of words in their writing.